Pengenalan Tanaman Hidroponik dengan Mengkreasi Limbah Plastik pada Siswa Sekolah Dasar - Ubaidillah, Mohammad; Puspito, Agung Nugroho; Suud, Hasbi Mubarak; Marvintha, Kirana Ndaru; Zaphora, Shineya Zennita; Hapsari, Salu Silvi; Firdaus, Rayhan Wahyu; Dewi, Ruli Kusuma; Amelia, Wirda Fransisca; Aprillianto, Bayu; Zahrosa, Dimas Bastara (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Hydroponics can be an alternative program for elementary or early childhood education as a form of effort to instill an entrepreneurial spirit in agriculture. In addition to raising the theme of hydroponics in community service, we display Go Green material, namely the use and management of plastic waste as a support in Hydroponics activities. Many benefits of the Hydroponics program and the utilization of plastic waste in schools are as follows. Introducing this hydroponic planting system as a new knowledge for students, increasing students' knowledge and insight about the use of plastic waste, and instilling the spirit of farming from an early age. The indicators of the achievement of community service activities are the active participation of SD Pejagan students during the activity and the last achievement is that students practice at their respective homes.